Development and reliability of cross-cultural dimension items, and marketability skills amongst Malaysian Technical University network future graduates - Nor Shela Saleh; Siti Khairizah Mohmed; Khairunesa Isa (Penerbit Universiti Kebangsaan Malaysia, 2023)
The issue of marketability among recent college graduates is regularly raised. Competition and economic problems have a substantial impact on graduates' ability to find work. As a result of this research, a tool that assesses cross-cultural dimensions and marketability skills will be developed to identify how potential graduates are perceived before they graduate from college. Respondents were randomly assigned questionnaires at three Malaysian Technical University Network (MTUN): Universiti Malaysia Pahang (UMP), Universiti Teknikal Malaysia Melaka (UTEM) and Universiti Malaysia Perlis (UniMAP). The samples are 44 prospective graduates from four MTUN universities. The responses from the samples provide acceptable and sufficient data for the pilot study's analysis of the study's dependability. The researcher has successfully developed a questionnaire instrument, and a pilot study analysis was carried out to ensure the validity and acceptance of the study as a construct. All cross-cultural dimensions have reliability above 0.6. Therefore, repeated analysis does not need to be done in a cross-cultural context. Several constructs of marketability have been dropped and analyzed, such as planning skills, problem-solving skills, communication skills, logical thinking skills, teamwork skills, and proactive skills. Other marketability constructs, namely technological skills and intrapersonal skills have reached a level of reliability above 0.6 and do not require repeated analysis. Finally, the pilot research for the instrument measuring future graduates' marketability abilities, as well as the cross-cultural component, was successfully completed. As a result, the researcher will use these evaluated items as instruments in the empirical field study.